1983
DOI: 10.1136/gut.24.8.724
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-containing nerve fibres in the gut wall in Crohn's disease.

Abstract: SUMMARY Neurones containing VIP, substance P, or enkephalin were studied by immunocytochemistry in intestinal specimens from 27 patients with Crohn's disease. Also several endocrine cell systems in the gut were examined. The results were compared with those from a control group of 26 patients. The relative frequency of various endocrine cells did not differ overtly from that in controls. Vasoactive intestinal polypeptide and substance P nerve fibres were distributed in all layers of the gut wall, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
4
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(44 citation statements)
references
References 16 publications
2
37
4
1
Order By: Relevance
“…there is an increase in the density of nerve elements containing VIP in the wall of the small and the large intestine [11,13]. On the other hand, observations related to the same disease suggest that there are no similar changes in the density of nerve elements containing VIP in the layers of the intestinal wall [29]. Results of other studies on Crohn's disease are completely different.…”
Section: Discussioncontrasting
confidence: 39%
“…there is an increase in the density of nerve elements containing VIP in the wall of the small and the large intestine [11,13]. On the other hand, observations related to the same disease suggest that there are no similar changes in the density of nerve elements containing VIP in the layers of the intestinal wall [29]. Results of other studies on Crohn's disease are completely different.…”
Section: Discussioncontrasting
confidence: 39%
“…The increase in argyrophil and chromogranin-immunoreactive cells might reflect the increase in serotonin-immunoreactive cells found in patients with UC and in serotonin-and enteroglucagon-immunoreactive cells in patients with CD. It has been reported previously [13] that no difference was found between patients with CD and controls concerning the number of colonic enterochromaffin, enteroglucagon and somatostatin cells. In the present study, however, both serotoninand enteroglucagon-immunoreactive cell areas were increased compared with the controls.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that the intestine of patients with ulcerative colitis (UC) and in those with Crohn's disease (CD) exhibits an abnormal immune response [7], motility disturbances [8] and increased permeability [9,10]. In order to find a possible aetiological factor and to increase our understanding of the pathophysiological processes involved in inflammatory bowel disease (IBD), the neuroendocrine regulatory system has been the subject of several studies [11][12][13][14][15][16][17][18][19][20]. Apart from a morphometric study on the serotonin-, enteroglucagon-and somatostatin-containing cells in patients with CD [13], these investigations have concentrated on the peptidergic nerve fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have not been able to confirm these findings. In one study, VIP immunoreactive nerves were found to be coarser in Crohn's disease compared with controls, but the levels of VIP were not elevated in the ileum and were significantly reduced in the colon (Sjolund et al, 1983). In other studies, VIP immunoreactive nerves were reduced in the colon in Crohn's disease (Kubota et al, 1992;Mazumdar and Das, 1992) and ulcerative colitis, (Kubota et al, 1992) as was the content of VIP measured by radioimmunoassay (Koch et al, 1987).…”
Section: Neuropeptidesmentioning
confidence: 96%